2008
DOI: 10.1161/circimaging.108.782086
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Diastolic Mechanical Dyssynchrony and Associated Clinical Outcomes in Children With Dilated Cardiomyopathy

Abstract: Background-We investigated diastolic mechanical dyssynchrony and its relation to clinical status in pediatric dilated cardiomyopathy (DCM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 29 publications
6
30
1
Order By: Relevance
“…We previously found that mechanical dyssynchrony effecting diastole was associated with poor outcomes in pediatric DCM. 26 Subsequent adult studies describing variations on this pattern analysis and using various terminology have shown strong CRT response predictive profiles. 9,17 Although a strong case is made for using strain pattern analysis to predict CRT response, CPD as a dichotomous analysis does not yet adequately differentiate the degree of mechanical dyssynchrony.…”
Section: Measuring Mechanical Dyssynchrony and Cpdmentioning
confidence: 99%
“…We previously found that mechanical dyssynchrony effecting diastole was associated with poor outcomes in pediatric DCM. 26 Subsequent adult studies describing variations on this pattern analysis and using various terminology have shown strong CRT response predictive profiles. 9,17 Although a strong case is made for using strain pattern analysis to predict CRT response, CPD as a dichotomous analysis does not yet adequately differentiate the degree of mechanical dyssynchrony.…”
Section: Measuring Mechanical Dyssynchrony and Cpdmentioning
confidence: 99%
“…Moreover, there are very few studies investigating DD in childhood CM, and these involve relatively small numbers of patients. [1][2][3]12 Consequently, diagnosis and grading of DD in childhood CM remains poorly defined. The aim of this study was to define problems in classification of DD in children with CM using echocardiography and to assess whether published adult echo guidelines for classification and grading of DD are applicable to this population.…”
Section: Clinical Perspective On P 261mentioning
confidence: 99%
“…[1][2][3] Although left ventricular (LV) ejection fraction (EF) correlates with patient outcomes in adults and children, echo parameters of DD are most predictive of outcome in pediatric dilated CM (DCM), 1,2 noncompaction, 4 and hypertrophic CM (HCM). 3,5,6 Therefore, echo diagnosis and grading of DD in childhood CM is important.…”
mentioning
confidence: 99%
“…Diastolic dyssynchrony is also impaired in patients with on-treatment hypertension or diabetes mellitus [3,4]. Diastolic dyssynchrony is associated with adverse clinical outcomes in patients with dilated cardiomyopathy [16]. Diastolic dyssynchrony improves in responders but not in nonresponders after cardiac resynchronization therapy (CRT) [15], resulting in reduction in morbidity and mortality [17].…”
Section: Introductionmentioning
confidence: 99%